Well-being of Diabetics in The Sultanate of Oman and its Relationship with some Variables - Al-Ghdani, Nasser Rashid; Sskamanya, Siraje Abdallah (Journal of Educational and Psychological Sciences, 2021)
The current study designed to disclose the level of psychological well-being of diabetics in the Sultanate of Oman, and also intended to know the nature of life during their diagnosis of diabetes, and to know the most complications of their disease, and the study also required to know the differences in psychological well-being according to variables: gender, type of treatment, And the duration of the injury, as the research sample consisted of (48) diabetic patients in the Sultanate of Oman. To fulfil the purpose of the study, the researcher applied the well-being prepared by (Al Ghadani 2020), and to process the data, the researcher used the Cronbach alpha coefficient, arithmetic averages, frequencies, and percentages. The study showed the following results: The level of psychological well-being among diabetics in the Sultanate of Oman was acceptable to a certain extent, for all dimensions of psychological well-being. The results showed that the nature of the life of diabetics after being diagnosed with the disease was bad. The most common complications among diabetics, first: visual destruction. second: sexual weakness, and foot disease, third: kidney and eating disorders, and fourth: heart and arteries. There were statistically between the average psychological well-being of diabetic patients in the Sultanate of Oman due to the gender variable. There were no statistically between the average psychological well-being of diabetic patients in the Sultanate of Oman due to the variable of treatment quality and duration of diabetes.